Thermophysical properties of NPG solid solution in the NPG-SCN organic system - Karadag, Saadet B.; Ozturk, Esra; Aksoz, Sezen; Marasli, Necmettin (CARL HANSER VERLAG, 2018)
A horizontal linear heat flow apparatus connected to an optical microscope was used to directly observe the grain boundary groove shapes of solid ncopentylglycol solution equilibrated with neopentylglycol-succinonitrile eutectic liquid at a constant temperature gradient. The thermal conductivity variations with temperaure for solid neopentylglycol solution and neopentylglycol-succinonitrile eutectic solid were measured with a radial heat flow apparatus. By using the observed grain boundary groove shapes and measured values of temperature gradients and thermal conductivity of solid phase and liquid phase, the values of the Gibbs Thomson coefficient, solid liquid interfacial energy and grain boundary energy were determined for the solid ncopentylglycol solution equilibrated with the neopentylglycol-succinonitrile eutectic liquid.
Keywords: Solidification; Interfaces; Phase equilibria; Surface processes; Organic compounds; LIQUID INTERFACIAL ENERGY; EUTECTIC LIQUID; PIVALIC ACID; NEOPENTYLGLYCOL; SUCCINONITRILE; AMINOMETHYLPROPANEDIOL; EQUILIBRIUM; ALLOYS; TEMPERATURE; Metallurgy & Metallurgical Engineering